Effect of excessive Arm Swing on Speed and Cadence of walking - Yousefian Molla, Razieh; Sadeghi, Heydar; Farahmand, Farzam; Azarbayjani, Mohammad Ali (Archives of Men's Health, 2020)
Introduction: One of the changes in the movement patterns that can be seen in upper limb swing is the excessive increase in upper limb movement and swing during walking. As temporal parameters such as cadence and speed in stationary and mobile environments can be equally used to determine early fall potentials, Therefore, this study aims to investigate the effect of excessive arm swing on speed and cadence of walking. Material and Methods: 30 healthy subjects were exposed to Vicon 10 motion capture system analysis and were asked to first walk normally at normal speeds and then move their hands excessively while walking at the same speed. The temporal data were extracted and analyzed by Matlab software. Descriptive (mean, SD) and Shapiro-Wilk test for normality of data distribution, and paired sample t-test were used to compare the patterns. Results: there was a significant difference in cadence and speed variables, between the means of natural arm swing and excessive arm swing modes (p ≤ 0.05). Conclusion: Given these results, it should be considered that the effects of upper limb pattern changes on the lower limbs and gait can compensate for the lack of attention to movement and pattern of upper extremity positioning during walking.